Reflexões sobre a pesquisa com grupos focais nas ciências sociais e humanas: a questão da quantidade de participantes, proveniência e local de organização - Ricardo Fernandes Pátaro; Geiva Carolina Calsa (Ciências Sociais Unisinos)
This article presents some issues about the focus groups from a doctoral research in education that used the focus group technique to study the teacher's representations. In the scientific literature we find guidelines for organizing focus groups in social and human sciences. These guidelines include the usual recommendations that focus groups should consist of 6 to 8 unknown participants, gathered in a neutral place. Although important, such conventions may lead to a tacit understanding that there would be an ideal way to work with focus groups. This article aiming at problematize these conventions presenting a research that used focusgroups out ofstandards, with 20 people who known each other in their daily work place. The results recall the importance of considering the research objectives when organizing focus group. From our experience, we conclude that conven-tions are more guidelines than prescriptions and we organize suggestions for conducting focus groups in human and social science research.